Biological Functions and Molecular Mechanisms of MiR-608 in Cancer - Lu, Juan; Zhu, Danhua; Li, Lanjuan (Frontiers in Oncology, 2022)
In recent years, microRNAs (miRNAs) have attracted much attention because of their prominent role in cancer. An increasing number of studies have shown that miRNAs play an important role in a variety of tumors. miR-608 has been reported to be decreased in cancers, especially in solid tumors. miR-608 is regarded as a tumor suppressor, which has been verified through a large number of experiments both in vivo and in vitro. miR-608 participates in many biological processes, including cell proliferation, invasion, migration, and apoptosis, by inhibiting transmembrane proteins and many signaling pathways. Here, we summarize the expression profile and biological functions and mechanism of miR-608, suggesting that miR-608 is an ideal diagnostic and prognostic biomarker and a treatment target for cancer.